Profil Kambing Kejobong Paritas Litter Size Dan Mortalitas Studi Kasus: Di KTT Ngudi Dadi Kecamatan Kejobong Kabupaten Purbalingga: Profile of The Kejobong Goats Based on Parity Litter Size and Mortality Case Study: in The Ngudi Dadi Livestock Farmer Group of Kejobong District Purbalingga Regency - Setiawan, Dika; Santosa, Setya Agus; Candrasari, Dewi Puspita (Fakultas Peternakan Universitas Jambi, 2023)
This study aims to determine the profile of Kejobong goat mothers based on parity, litter size, and mortality and the relationship between parity and litter size and the life force of children in Kejobong District, Purbalingga Regency, precisely the Ngudi Dadi Livestock Farmer Group which is the center of Kejobong goat development. The material used was 70 mothers and 121 Kejobong goat cubs. The research method used is aÂ survey method with purposive sampling data collection techniques. The data obtained were analyzed using qualitative descriptive analysis by grouping each variable. The results showed that the mother goat Kejobong had entered the first parity of 21.43%, the second parity of 44.28%, the third parity of 28.57% and the fourth parity of 5.72% with litter size one 32.86% litter size two 61.43%, and litter size three 5.71% of the life force of the children born by 84.30%Â and mortality of 15.70%. Based on research, it can be concluded that the most parity is the second parity,Â the most litter size is two tails, mortality is relatively low and parity does not affect litter size and life force.